Analisis Pembelajaran Steam (Science, Technology, Engineering, Art, And Mathematics) Terhadap Aktivitas dan Hasil Belajar Ekonomi Kelas XI IPS SMA Negeri 1 Sompak - Irfani Surya Permana; Junaidi H. Matsum; Syamsuri; Husni Syahrudin; Muhammad Basri (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
STEAM (Science, Technology, Engineering, Arts, and Mathematics) is a learning approach that integrates these five fields into one learning context and aims to improve the learning activities and learning outcomes of students at 1 Sompak State High School. Research methods used experimental data collection techniques using observation, testing, and documentation. Data analysis techniques include normality tests, homogeneous tests, and differential tests. From the observations of the students's learning activities in the experimental class after being treated, it was found that the average percentage of student learning activities was 91.48% in the experimental class with high criteria, while the average student learning activities in the control class were 79.73%. The learning outcomes of students in experimental classes using the learning approach STEAM (Science, Technology, Engineering, Art, and Mathematic) were better known than the learning outcomes of the students in control classes that applied the teaching method. This was proven by the average posttest score of students in the experimental class of 85.81 while in the control class of 76.00. The hypothesis test using the Levene test for the data of the student's learning activity calculated using an independent sample t test with the Mann-Whitney U statistical test on SPSS 26 yielded a significance of 0.000, thus Ha was accepted because the significance value obtained was < 0.05. The calculation of the Man-Witney U study with the program version 26 showed an asymptotically . significant . (2-tailed) value of 0,004. See also Table 4.11, where the mean column ranks the learning outcomes in the experimental class at 37.15 higher than the control class, which is only 24.65. The conclusion is that learning STEAM is better than learning with lectures.